The role of community institutions in the management of water infrastructure in the context of Madhya Pradesh, India - Falk, Thomas; Duche, Vishwambhar; S., Suhas K.; Agrawal, Ishan; Bartels, Lara (Indian Water Resources Society, 2020)
Since the 1990s, India substantially invested in participatory watershed development. An important element of related projects is the rehabilitation of small-scale water harvesting infrastructure.Despite its multipleeconomic and ecologicalbenefits, many communities fail to sustainably manage the structures. Among other factors, a favorable local institutional framework has been identified as a critical precondition for improving the management. This is more critical when common-pool resources are affected which are prone to social dilemmas. Typically mechanisms to support communities in this regard are blueprint solutions such as community water funds or organizational capacity development of Water User Associations. Little attention is paid to supporting communities in developing rules related to water and water infrastructure management. The latter requires a good understanding of local water management rules. This paper assesses the rules related to common water infrastructure in a case in Madhya Pradesh/India. The presented research uses four sources of data which are a) key informants’ interviews, b) individual interviews, c) discussions from a learning game intervention, and d) Foundation for Ecological Security (FES) data. This is relevant from a water management perspective as it may hint at entry points for community-based governance mechanisms. The paper demonstrates a simple assessment framework which can be applied across South Asia and can be input to improving the sustainability of future watershed programs. Our assessment revealed multiple examples of rules related both to the maintenance of water infrastructure and the utilization of water. There is evidence that some farmer invest in maintaining the structures. This indicates that possible solutions are not far to seek. However, the existence of rules and reports on maintenance efforts are not reflected in the state of the infrastructure. There is a need to better understand under which conditions communities manage to establish effective water governance that effectively improves management.